2006
DOI: 10.1080/00288330.2006.9517422
|View full text |Cite
|
Sign up to set email alerts
|

Lack of divergence in the mitochondrial cytochromebgene betweenMacruronusspecies (Pisces: Merlucciidae) in the Southern Hemisphere

Abstract: Two species of grenadier, the blue grenadier (or hoki) Macruronus novaezelandiae and the Patagonian grenadier M. magellanicus, have been recorded in the Southern Hemisphere with disjunct distributions along southern Australia-New Zealand and southern Chile-Argentina, respectively. The extent of genetic difference between these two putative species was examined using partial sequences (n = 44; 405 bp) of the mitochondrial DNA cytochrome b gene in a phylogenetic analysis and in an analysis of molecular variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…The previous results from sequence analyses of protein-coding genes for the two species of grenadier also showed a lack of genetic differentiation between species (Olavarría et al, 2006;Ward, 2009). These results challenge the idea that the two pairs of the closely related gadiform fishes represent two distinct species and subspecies, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…The previous results from sequence analyses of protein-coding genes for the two species of grenadier also showed a lack of genetic differentiation between species (Olavarría et al, 2006;Ward, 2009). These results challenge the idea that the two pairs of the closely related gadiform fishes represent two distinct species and subspecies, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…However, they retained M. capensis because they were unable to examine material of this species. The molecular study of Olavarría et al (2006) confirmed the synonymy of M. magellanicus and M. novaezlandiae. These authors also excluded M. capensis from their analysis, accepting its validity with the caveat that the nature of the studies by Inada (1990) and Lloris et al (2003) precluded a reevaluation of their decisions.…”
Section: Introductionmentioning
confidence: 59%
“…Olavarría et al's (2006) molecular study, using cytochrome b data from the same fragment, argued for the status of M. magellanicus as a junior synonym of M. novaezelandiae, based on the lack of differentiation among the two populations; a shared haplotype was the most abundant in both species, and low levels of population differentiation were only due to rare haplotypes within each. In the present case, the M. capensis cytochrome b haplotype is identical to this shared, common haplotype in M. magellanicus (Olavarría et al 2006) and M. novaezelandiae (Baker et al 1995;Olavarría et al 2006). While the analysis of a single specimen precludes a more detailed consideration of population differentiation, the comparison of this sequence to other sequences from M. magellanicus reveals this divergence to be no more extensive than divergences among the M. magellanicus sequences themselves.…”
Section: Morphologymentioning
confidence: 77%
See 2 more Smart Citations